2009
DOI: 10.5137/1019-5149.jtn.1681-09.3
|View full text |Cite
|
Sign up to set email alerts
|

Fractionated gamma knife radiosurgery for optic nerve tumors: a technical report

Abstract: Fractionated regimens of Gamma Knife surgery offer a very good alternative for lesions such as optic glioma and optic nevre sheath meningioma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 22 publications
0
11
0
1
Order By: Relevance
“…85 Stereotactic radiosurgery (SRS) is the most recent treatment modality used in optic nerve gliomas and a handful of case reports have recently been published describing its use. [86][87][88][89] Although small in number, SRS was well tolerated and tumour control was achieved in all patients. No patient developed tumour progression or recurrence following treatment with SRS but the length of follow-up in these patients was significantly shorter (maximum.…”
Section: Radiotherapymentioning
confidence: 91%
“…85 Stereotactic radiosurgery (SRS) is the most recent treatment modality used in optic nerve gliomas and a handful of case reports have recently been published describing its use. [86][87][88][89] Although small in number, SRS was well tolerated and tumour control was achieved in all patients. No patient developed tumour progression or recurrence following treatment with SRS but the length of follow-up in these patients was significantly shorter (maximum.…”
Section: Radiotherapymentioning
confidence: 91%
“…61 Initial reports of successful treatment of ONSM using multi-session radiosurgery show some promise but have had few patients with limited follow-up. 61,62 Recently, Matchetti et al reported their series of 21 patients treated with CyberKnife in five fractions of 5 Gy each with 35% visual improvement and no late toxicities at 30-month followup. 63 While this technique may eventually become a viable alternative to fractionated conformal radiotherapy, further studies are required to assess the efficacy and safety to the optic nerve as compared to the current standard of care.…”
Section: Stereotactic Radiosurgerymentioning
confidence: 98%
“…Radiation therapy with fractionated gamma knife radiosurgery can be used after chemotherapy failure and retards or reverses progress in many cases. However, long term-data does not suggest that this specifically reduces mortality or vision loss [60]. Radiation treatment also exposes the patient to the potential side effects of radiation treatment, including dry eye, neovascular glaucoma, cataract, retinopathy, and optic neuropathy.…”
Section: Orbital Neoplasmsmentioning
confidence: 99%